How fresh is fresh? Perceptions and experience when buying and consuming fresh cod fillets - Østli, J. (2012)
From January 1st 2010 it was mandatory for all retail stores selling fresh fish in Norway to provide their customers with capture date information for wild fish and slaughter date for farmed fish. The objectives of this study were to: (a) evaluate how many days after capture are consumers willing to buy fresh fish stored on ice, (b) once they have bought the fish how many days are they willing to keep it at home before eating it, and (c) estimate the shelf life of fresh cod using consumer acceptance/rejection data, with and without capture-date information. To cover (a) and (b) a survey was conducted in Norway among 419 respondents visiting retail stores asking them to evaluate how many days after capture they were willing to buy fresh Atlantic cod (Gadus morhua) stored on ice. The respondents were also asked how many days after purchase they were willing to keep the fresh cod at home before cooking and eating it. To cover objective (c), fillets of wild Atlantic cod were evaluated by a total of 389 consumers from three Norwegian cities in three different stages: raw and cooked without information on capture data, raw with capture date information. Survival analysis statistics were used to analyze the data with the inclusion of respondents’ age, self-reported degree of fresh fish expertise and frequency of fresh fish consumption. When respondents were asked for the last day they would buy fresh cod after capture, there was a 75% probability that this would be approximately 3 days and 5 days for elder and young respondents, respectively. There was a 75% probability that these respondents would have the fish approximately 1 day at home before cooking and eating it. The shelf life (as measured in an acceptability test) corresponding to a 25% rejection probability was approximately 7 days and 11 days, with and without capture-date information, respectively. Thus, in general, when respondents were asked which was the last day they would be willing to buy cod after capture, this time (3–5 days) was shorter than the shelf life (7–11 days).